2013
DOI: 10.3724/sp.j.1141.2012.02231
|View full text |Cite
|
Sign up to set email alerts
|

Locomotor activity and learning and memory abilities in Alzheimer’s disease induced by Aluminum in an acid environment in Zebrafish

Abstract: Abstract:We investigated the contribution of locomotor activity and learning and memory abilities to Alzheimer's disease induced by metal neurotoxicity. The metal neurotoxicity model was established by using locomotor activity tests and activity-avoidance conditioning paradigms, and observing changes in zebrafish behaviors after exposure to 50 µg/L of AlCl 3 with different pH values (pH 7.8, pH 6.8 and pH 5.8) for 24 hours and 96 hours. The results showed Alzheimer's disease-like behavior in locomotor activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…Learning and memory deficits have also been observed in these fish 106 . Zebrafish treated with Aluminium in an acid environment displayed behaviour with AD-like condition wherein their locomotor activity and learning ability got abrogated 107 . Furthermore, it has been reported that intraventricular injection of Aβ 1–42 in the embryonic brain leads to memory loss and cognitive deficits along with increased Tau phosphorylation 104 , 108 .…”
Section: Zebrafish As An Ad Modelmentioning
confidence: 99%
“…Learning and memory deficits have also been observed in these fish 106 . Zebrafish treated with Aluminium in an acid environment displayed behaviour with AD-like condition wherein their locomotor activity and learning ability got abrogated 107 . Furthermore, it has been reported that intraventricular injection of Aβ 1–42 in the embryonic brain leads to memory loss and cognitive deficits along with increased Tau phosphorylation 104 , 108 .…”
Section: Zebrafish As An Ad Modelmentioning
confidence: 99%
“…Zebrafish have been used extensively in the creation of animal AD models to better understand the pathology of the disease. Alzheimer's in zebrafish has been induced via both neuropharmacological [213][214][215][216] and genetic means [91,[217][218][219]. Such models have been invaluable in the conduct of research geared towards finding targets for treatment.…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…Além disso, foi relatado que a injeção intraventricular de Aβ 1-42 no cérebro embrionário leva à perda de memória e déficits cognitivos, juntamente com o aumento da fosforilação de Tau. O zebrafish está, portanto, emergindo como um modelo poderoso para pesquisa no campo da neurofarmacologia (BEST et al, 2008;NERY et al, 2014;CHEN et al, 2011;NADA;WILLIAMS;SHAH, 2016;HE;ZHONG;CHE, 2012;PAQUET;SCH-MID;HAASS, 2010).…”
Section: Zebrafish Como Modelo Para Daunclassified